2022
DOI: 10.3390/ijms23094965
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of High-Affinity Nitrate Transporter 2 (NRT2) Gene Family in Brassica napus

Abstract: Nitrate transporter 2 (NRT2) plays an essential role in Nitrogen (N) uptake, transport, utilization, and stress resistance. In this study, the NRT2 gene family in two sequenced Brassica napus ecotypes were identified, including 31 genes in ‘Zhongshuang11’ (BnaZSNRT2s) and 19 in ‘Darmor-bzh’ (BnaDarNRT2s). The candidate genes were divided into three groups (Group I−III) based on phylogenetic analyses, supported by a conserved intron-exon structure in each group. Collinearity analysis revealed that the large exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Contrarily, NRT2 family plays an imperative role in NO 3 acquisition under N deficient conditions (Zou et al, 2020;Li et al, 2022b;Du et al, 2022). For instance, NO 3 transporter-like NRT2.1, NRT2.2, NRT2.4, and NRT2.5 require a partner protein, NAR2.1 (Kiba et al, 2012;Lezhneva et al, 2014;Zou et al, 2020) in Arabidopsis to acclimatize under such conditions.…”
Section: Gene Expression Action Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, NRT2 family plays an imperative role in NO 3 acquisition under N deficient conditions (Zou et al, 2020;Li et al, 2022b;Du et al, 2022). For instance, NO 3 transporter-like NRT2.1, NRT2.2, NRT2.4, and NRT2.5 require a partner protein, NAR2.1 (Kiba et al, 2012;Lezhneva et al, 2014;Zou et al, 2020) in Arabidopsis to acclimatize under such conditions.…”
Section: Gene Expression Action Referencesmentioning
confidence: 99%
“…For instance, NO 3 transporter-like NRT2.1, NRT2.2, NRT2.4, and NRT2.5 require a partner protein, NAR2.1 (Kiba et al, 2012;Lezhneva et al, 2014;Zou et al, 2020) in Arabidopsis to acclimatize under such conditions. In addition, other transporters such as CmNRT2.1 in Chrysanthemum indicum (Chrysanthemum; Gu et al, 2016), TaNRT2.1-6B in wheat (Li et al, 2022a), BnaZSNRT2s in Brassica napus (Canola; Du et al, 2022) and OsNRT2.1, OsNRT2.2, OsNRT2.4 and their partner protein OsNAR2.1 in rice (Naz et al, 2019;Souza et al, 2022) also function as NO 3 influx transporters (Figure 2). Among all NO 3 transporters, the dual affinity NO 3 transporter NRT1.1 (AtNPF6.3) serve as a multifunctional protein with a critical role in both NO 3 acquisition and sensing.…”
Section: Gene Expression Action Referencesmentioning
confidence: 99%
“…NRT2 homologous proteins are typical high-affinity nitrate transporters in the plant kingdom and are responsible for the nitrate uptake process in plants. In general, NRT2 proteins (NRT2s) have a typical membrane topology connected by a cytosolic loop, including 1 MFS domain that exhibits dual affinities for nitrate 18 and 12 transmembrane domains 19 , which are usually located on the cell plasma membrane 20 . Lots of NRT2 members have been identified in Nicotiana tabacum, Glycine max, Arabidopsis thaliana, Solanum lycopersicum, Oryza sativa, Zea mays, Triticum aestivum, and so on [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, numerous studies have investigated the functional roles of the plant NRT2 family and important progress has been made. It has been reported that there are 7 NRT2 genes in Arabidopsis [10,16], 4 in rice [17], 4 in maize [18], 31 in Brassica napus [19,20], 13 in poplar [21], 4 in tomato [22], and 5 in wild soybean (Glycine soja) [23]. In Arabidopsis, four AtNRT2 transporters (AtNRT2.1, AtNRT2.2, AtNRT2.3, and AtNRT2.4) are involved in nitrate uptake.…”
Section: Introductionmentioning
confidence: 99%